Baby Dance - Taylor, Ann, 1782-1866; Van Heerden, Marjorie (New York : HarperFestival, 1999)
"All babies love to be lifted, twirled, and held in loving arms. Now a rhythmic poem by nineteenth-century poet [Ann] Taylor [appears in a] board book ... for baby and parent to share"--Amazon.com.
Keywords: Father and child -- Juvenile fiction; Infants -- Juvenile fiction; Father and child -- Fiction; Babies -- Fiction; Stories in rhyme; Stories in rhyme